1982
DOI: 10.1001/archderm.118.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The role of depilation and deodorants in hidradenitis suppurativa

Abstract: Shaving and the use of chemical depilatories, deodorants, and talcum powder have been implicated in the initiation of hidradenitis suppurativa. This study compared the use of these agents in the axillae and puboinguinoperineal (hereinafter called the inguinal) region of 40 patients with hidradenitis, prior to the onset of the condition, with their use in normal age- and sex-matched controls. No significant differences in the application of shaving, chemical depilatories, or deodorants at either site in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…A conclusive demonstration, however, requires proof of a temporal relationship and an improvement in HS following weight loss. Antiperspirant, talc, and deodorant use and depilation with a safety razor have been ruled out as pathogenic factors [10]. Tight clothing may contribute to discomfort and is considered a triggering factor by some authors.…”
Section: Risk Factorsmentioning
confidence: 99%
“…A conclusive demonstration, however, requires proof of a temporal relationship and an improvement in HS following weight loss. Antiperspirant, talc, and deodorant use and depilation with a safety razor have been ruled out as pathogenic factors [10]. Tight clothing may contribute to discomfort and is considered a triggering factor by some authors.…”
Section: Risk Factorsmentioning
confidence: 99%
“…28 Two studies have been unable to identify differences in the pattern of use of cosmetics, shaving, or use of talcum in HS. 28,92 Histological data which could substantiate an irritant component of early HS provide mixed results. One study found infrainfundibular spongiosis in early lesions, while another study found no signs of irritant reactions (spongiosis or parakeratosis).…”
Section: Infectionmentioning
confidence: 99%
“…Time for complete wound healing for patients treated by excision and second intention healing varied proportionally to the extent and degree of infection of the unroofed area, with a mean of ten weeks (range, 7-17 weeks). In the patients treated by excision and skin grafting, the time until complete healing was shorter, with a mean of six (range, [3][4][5][6][7][8][9] weeks. Partial loss of the skin graft occurred in nine (37.5 percent) patients treated with this technique.…”
Section: Resultsmentioning
confidence: 99%